Application of Hybrid Cubic B-Spline Collocation Approach for Solving a Generalized Nonlinear Klien-Gordon Equation - Zin, Shazalina Mat; Majid, Ahmad Abd; Ismail, Ahmad Izani Md.; Abbas, Muhammad (Hindawi Publishing Corporation, 2014)

(untitled)
The generalized nonlinear Klien-Gordon equation is important in quantum mechanics and related fields. In this paper, a semiimplicit approach based on hybrid cubic B-spline is presented for the approximate solution of the nonlinearKlien-Gordon equation. Theusual finite difference approach is used to discretize the time derivativewhile hybrid cubic B-spline is applied as an interpolating function in the space dimension.The results of applications to several test problems indicate good agreement with known solutions.